2000
DOI: 10.1023/a:1009201426184
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Thyroid function tests (serum levels of thyroxine-T4, triiodothyronine-T3 and thyroid stimulating hormone-TSH) were performed in fifty-eight men (mean age: 31.7 +/- 10.6 years; mean duration of lead exposure: 156.9 +/- 122.7 months). These subjects were exposed to lead either as petrol pump workers or automobile mechanics. The mean whole blood lead (Pb-B) levels were 2.49 +/- 0.45 micromole/l (51.90 +/- 9.40 microg/dl) in the lead exposed workers and were approximately 5 times higher than in the control (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Pb exposure [mean 15 µg/dL blood Pb (BPb) level] was negatively correlated with transthyretin levels in cerebrospinal fluid samples from human patients (Zheng et al 2001). Previous studies of populations with high exposure to Pb (indicated by BPb levels of > 20 µg/dL) suggested negative associations with circulating T 4 , FT 4 , or T 3 (López et al 2000; Robins et al 1983; Singh et al 2000; Tuppurainen et al 1988); however, associations were not evident in other similar study populations (Erfurth et al 2001; Schumacher et al 1998; Siegel et al 1989). Fewer studies have investigated associations of BPb levels of < 10 µg/dL with THs.…”
mentioning
confidence: 70%
“…Pb exposure [mean 15 µg/dL blood Pb (BPb) level] was negatively correlated with transthyretin levels in cerebrospinal fluid samples from human patients (Zheng et al 2001). Previous studies of populations with high exposure to Pb (indicated by BPb levels of > 20 µg/dL) suggested negative associations with circulating T 4 , FT 4 , or T 3 (López et al 2000; Robins et al 1983; Singh et al 2000; Tuppurainen et al 1988); however, associations were not evident in other similar study populations (Erfurth et al 2001; Schumacher et al 1998; Siegel et al 1989). Fewer studies have investigated associations of BPb levels of < 10 µg/dL with THs.…”
mentioning
confidence: 70%
“…Although, the present study did not evaluate histological changes in the thyroid glands, Pb on its own has been shown to cause hypothyroidism either by inhibiting iodine uptake [25, 26] and to cause functional impairment of the pituitary—thyroid axis [27]. …”
Section: Discussionmentioning
confidence: 99%
“…The same was observed for T3; an increase [ 456 , 457 , 458 , 462 , 464 ], decrease [ 455 , 463 ] or no change [ 458 , 459 , 460 , 461 ] after cadmium exposure. Lead exposure caused an increase [ 460 , 461 , 465 , 466 , 467 ], a decrease [ 318 , 351 , 468 ] or no change [ 423 , 454 , 457 , 458 , 459 , 469 , 470 , 471 , 472 , 473 , 474 , 475 ] in TSH levels. Likewise, an increase [ 458 , 468 , 476 , 477 ], a decrease [ 318 , 458 , 465 , 470 , 473 , 478 ] or no change [ 351 , 423 , 457 , 459 , 460 , 461 , 465 , 466 , 469 , 471 , 472 , 474 ...…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%